Tingkat Subjective Well-Being dan Tingkat Stres Mahasiswa di Masa Pandemi Covid-19 (Studi Pada Mahasiswa Organisasi Intra Kampus di UIN Malang) - Jiharudin, Jiharudin (LoroNG: Media Pengkajian Sosial Budaya, 2021)
There is a virus outbreak COVID-19 which has attacked almost the entire world has caused changes in various sectors, one of which is in the education sector. One of the people who feel the impact of this condition is students. Several research results found that the mental condition of students during the COVID-19 pandemic was not good, as evidenced by high levels of stress. In general, online learning, social distancing, PPKM, and others due to the COVID-19 pandemic have disrupted student activities, especially activities carried out on campus such as intra-campus organizational activities. This has an impact on the mental condition of students. This study aims to determine how the mental health picture is manifested in the level of subjective well-being and stress levels of students who participate in intra-campus organizations during the COVID-19 pandemic. This research takes the locus at UIN Malang. The method used in this research is a descriptive quantitative method using PANAS and SWLS measuring instruments for subjective well-being and K10 for stress. Everything was distributed via google form and the results were analyzed by univariate analysis using SPSS 22.00. The results showed that the subjective well-being level of students who participated in intra-campus organizations during the COVID-19 pandemic was at a moderate level, while the stress level was at a high level. Adanya wabah virus COVID-19 yang menyerbu hampir seluruh dunia mengakibatkan perubahan di berbagai sektor, salah satunya adalah sektor pendidikan. Salah satu yang merasakan dampak dari kondisi ini ialah mahasiswa. Beberapa hasil penelitian menemukan bahwa kondisi mental mahasiswa di masa pandemi COVID-19 kurang baik, dibuktikan dengan tingkat stress yang tinggi. Secara umum, belajar daring, social distancing, PPKM, dan lain-lain akibat pandemi COVID-19 menyebabkan kegiatan mahasiswa terganggu, terutama kegiatan yang dilakukan di lingkungan kampus seperti kegiatan organisasi intra kampus. Hal ini, berdampak pada kondisi mental mahasiswa. Penelitian ini bertujuan untuk mengetahui bagaimana gambaran kesehatan mental yang terwujud dalam tingkat subjective well-being dan tingkat stress mahasiswa yang mengikuti organisasi intra kampus pada masa pandemi COVID-19. Penelitian ini mengambil locus di UIN Malang. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif deskriptif dengan penggunaan alat ukur PANAS dan SWLS untuk subjective well-being dan K10 untuk stress. Semuanya disebarkan melalui google form dan hasilnya dianalisis dengan analisis univariat menggunakan bantuan SPSS 22.00. Hasil penelitian menunjukan bahwa tingkat subjective well-being mahasiswa yang mengikuti organisasi intra kampus pada masa pandemi.